KOMBINASI AUDIOVISUAL DAN PENYULUHAN TERHADAP PENINGKATAN PENGETAHUAN DAN SIKAP DALAM PENCEGAHAN FILARIASIS - Tambunan, Jansen Parlaungan; Mobalen, Oktovina (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2020)
Filariasis patient in West Papua province showed increased numbers from year to year. At the 12 districts/cities in West Papua, South Sorong as the highest areas with the Filariasis, followed by Monokwari, Wondama Bay, Maybrat, Sorong, Fak-Fak, Monokwari South, Tambrauw, Kaimana, Sorong, Bintuni Bay, and Raja Ampat. This is due local community do not have sufficient knowledge for the prevention of the Filariasis because lack of information about the Filariasis disease, negative attitude of the head family and behavior of the people who do not care for the prevention of Filariasis, lack attention againts the environment, and the different individual characteristics in several places. This type of research is semi-experimental study (Quasi Experiment) with Non Randomized Control group pretest-posttest design. The population in this study is Mariat community health centers in the region of the District Mariat numbered 30 people. The collected data is processed and analyzed using SPSS. The results showed there are differences in knowledge after use audiovisual combination with counseling in the prevention of Filariasis in Sorong district community. Value of p (t test) knowledge = 0.027<0.05. Percentage to increased knowledge in the prevention of Filariasis in the health centers Mariat Sorong is 0.5482 = 0.300 (30.03%). This means that 30.03% have increase knowledge in the prevention of Filariasis in the region Sorong Mariat health centers affected by the audiovisual combination and counseling. Suggested can be used by the clinic in order to improve the counseling applicable in the prevention of Filariasis as well as the behavior of the community itself that is based on knowledge. Awareness and a positive attitude in the prevention of Filariasis. And for further researchcan focus on research related to the development of vector and demographic differences in the spread of Filariasis cases.